Poverty and the social participation of young people—an analysis of poverty-related withdrawal mechanisms - Andreas Damelang; Georgi Kloß (Journal for Labour Market Research, 2013)
This paper analyses poverty-specific withdrawal mechanisms of children and adolescents. A lower social participation rate in extracurricular organisations decreases opportunities for informal learning and consequently reduces life chances. Poverty research has demonstrated that financial constraints and the social withdrawal that result from feelings of shame cause lower participation rates. By dividing extracurricular leisure activities into fee-based and non-contributory activities, it is possible to discriminate between the two mechanisms. Our empirical cross-sectional analysis is based on the panel study 'Labour Market and Social Security' (PASS). The results demonstrate that primarily financial shortages explain decreased participation opportunities and to a substantially lesser extent social withdrawal. Additionally, the findings suggest that social deprivation occurs only in situations of long-lasting poverty.
Keywords: J2; J23; J63; D22; 330; Jugendliche; Armut - Auswirkungen; soziale Partizipation; IAB-Haushaltspanel; soziale Ausgrenzung; ökonomische Faktoren; soziale Deprivation; Chancengleichheit; informelles Lernen; junge Erwachsene; Freizeitmöglichkeiten